Beloborodova Elvira Ivanovna - article Editorial (Бюллетень сибирской медицины, 2003)
In the article it is presented the biography of the outstanding Russian scientist-clinician, physician, professor of Siberian State Medical University, head of therapeutics chair of the faculty of raising the level of skill and postdiploma training, honoured doctor of Russia E.I. Beloborodova.